Augmentasi dan Reduksi dalam Visualisasi Materi SPI oleh Siswa SDN2 Bumiharjo dalam Format Flipbook - Nurhidayati, Erna; Khuriyah, Khuriyah (Al-Wasathiyah: Journal of Islamic Studies, 2025)
This study aims to explore how augmentation and reduction are applied by fifth-grade students at Bumiharjo 2 Elementary School in visualizing the History of Islamic Civilization through digital flipbooks. This research was motivated by students' low interest in religious history lessons, which tend to be delivered in a monotonous manner. The method used was descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The research subjects consisted of 10 fifth-grade students who created a flipbook project themed around the exemplary stories of the Prophets David, Solomon, Ilyas, Ilyasa, and Muhammad. The results showed that augmentation was often carried out by students with a strong visual learning style by adding visual elements such as symbols, expressions, and color to strengthen the story content. Meanwhile, reduction was found in students with auditory and kinesthetic learning styles who tend to simplify information into symbols, icons, or sequences of action images. Flipbooks serve as a creative medium that reflects students' thinking and understanding of the Prophet's exemplary values. This study concluded that flipbooks not only enrich students' learning experiences but also develop critical thinking skills, digital literacy, and spirituality in Islamic Religious Education (IS).